High sensitive troponin T as gatekeeper for cardiac magnetic resonance imaging in patients with suspected acute myocarditis. (25th November 2020) - Frick, M; Bauermann, K; Kirschfink, A; Hamada, S; Weber, O; Marx, N; Altiok, E
Abstract: Background: The diagnosis of acute (AM) is difficult because of the variable, unspecific clinical presentation. Cardiac magnetic resonance (CMR) is the noninvasive gold standard diagnostic tool, but limited availability and high costs make a quick and inexpensive test necessary to clarify the need for CMR. Quantification of high sensitive Troponin T (hsTNT) is a broadly available, specific blood test for cardiomyocyte damage. Aim: The aim of this study was to evaluate hsTNT as a gatekeeper for CMR with a lower cut off-value for exclusion and an upper cut-off value for confirmation of acute myocarditis as defined by CMR. Methods: This retrospective analysis included 244 patients (age 39±17 years, 71% male) who received CMR for clinically suspected AM and quantification of hsTNT within 28 days (Median: 2 days) of CMR. CMR (1.5 Tesla) consisted of cine-sequences, edema-sensitive T2 and late gadolinium enhancement (LGE) imaging. AM was diagnosed in presence of both, myocardial edema and LGE consistent with acute myocarditis. Results: Of 244 patients, 78 (32%) were CMR-positive (CMR+) for AM. 166 (68%) were CMR negative (CMR−). Mean hsTNT was 206±454 pg/ml. HsTNT was significantly higher in CMR+ than in CMR− (604±639 pg/ml vs 20±56 pg/ml, p<0.001, see figure A). 8 CMR+ patients (10%) had hsTNT in the normal range (<14 ng/ml). HsTNT showed good discriminatory performance in the Receiver Operator Characteristic (ROC) analysis (AUC 0.91, see figure B). A lower cut-off value of 4 pg/ml had a sensitivity of 98.7% for diagnosis of AM (hsTNT ≥4 pg/ml) and a negative predictive value of 98.2% for rule out of AM (hsTNT<4 pg/ml) as defined by CMR, leading to a reduction of 23.4% of CMR exams. An upper cut-off value of >343 pg/ml had a specificity of 99.4% and positive predictive value of 97.8% for diagnosis of AM, leading to a reduction of 18.4% of CMR exams (see table). Conclusions: hsTNT showed good discriminatory capacity for acute myocarditis (AM) as defined by CMR. However, 10% of patients had hsTNT in the normal range (<14 pg/ml). A lower cut-off value of <4 pg/ml ruled out AM with very high negative predictive value, whereas an upper cut-off of >343 pg/ml had a very high positive predictive value for confirmation of AM as defined by CMR. Performing CMR only in patients with hsTNT between 4 and 343 pg/ml would have led to a reduction of 41.8% of CMR exams. Funding Acknowledgement: Type of funding source: None